Forensic accounting - Hopwood, William S.; Leiner, Jay J.; Young, George R. (Boston: McGraw-Hill, 2009)
The book provides the most comprehensive view of fraud investigation on the market. Where other books focus almost entirely on auditing and financial reporting, Hopwood includes a vast range of civil and criminal accounting fraud and related activities, from false business valuations and employer fraud to information security and counter-terrorism. The author team's experience in fraud investigation lends the book a real-world perspective unmatched by any other textbook.
Includes Index
lje 6/9/13
Loans
Keywords: Forensic Accounting